Implementation of “Pecel Jawara Madiun” in Character Education through Holistic Approach to Elementary School Learners - Desita Anggi Harumsari; Winarno Winarno; Joko Daryanto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
This research describes the implementation of "Pecel Jawara Madiun" in the profile of Pancasila students (P3). The main objective of the research is to describe "Pecel Jawara Madiun" in strengthening the Pancasila student profile strengthening project (P5). The type of research is descriptive qualitative. Data collection methods with observation and interviews. Data analysis technique with inductive technique. Research results: the implementation of character education through internal and external strategies. Internal strategies are focused on storytelling and nembang jawa habituation activities aimed at building a school environment atmosphere. External strategies are focused on developing the school education system